MODERN PEDAGOGICAL APPROACHES TO THE TEACHING OF TRADITIONAL SINGING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The essence of modern pedagogical approaches to teaching traditional singing and their importance in the educational process are widely covered in this article. It analyzes the use of innovative methods, interactive methods and multimedia technologies aimed at developing students' creative activity, musical thinking and performing culture. It also identifies ways to strengthen the interaction between teacher and student, and to improve the effectiveness of teaching based on individual approaches and reflection. The results of the article serve to further improve the quality of teaching singing science.